Pengaruh Penyuluhan Identifikasi Pasien dengan Menggunakan Media Audiovisual terhadap Pengetahuan Pasien Rawat Inap - Roymond H. Simamora (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the effect of audiovisual media application of patient identification implementation on patient knowledge at the University of North Sumatra Hospital in 2019. The study used a quantitative approach, with quasi-experimental methods, one group pre-test-post-test design. The results showed that before counseling, 40 patients included in the category of sufficient knowledge, and 80 people in the category of insufficient knowledge. After counseling using audiovisual media, data obtained that, as many as 12 patients included in the category of good knowledge, 68 people in the category of sufficient knowledge, and 40 people in the category of lack of knowledge. These results indicate that there was an increase in the number of patients in the knowledge category. Conclusion, there is an influence of counseling given by the use of audiovisual media to increase the number of patients in the knowledge category. Keywords: Patient Identification, Audiovisual Media, Counseling